A Family Case Report of Niemman Pick C with New Mutation and Different Presentations - SHALBAFAN, Bita (Iranian Journal of Child Neurology, 2015)
How to Cite this Article: Shalbafan B. A Family Case Report of Niemman Pick C with New Mutation and Different Presentations. Iran J Child Neurol. 2015 Autumn;9:4(Suppl.1): 20-21. Pls see pdf.